BRAF V600E mutations in right-side colon cancer: Heterogeneity detected by liquid biopsy. Issue 6 (June 2022) - Ueda, Koji; Yamada, Takeshi; Ohta, Ryo; Matsuda, Akihisa; Sonoda, Hiromichi; Kuriyama, Sho; Takahashi, Goro; Iwai, Takuma; Takeda, Kohki; Miyasaka, Toshimitsu; Shinji, Seiichi; Chika, Noriyasu; et al.
Abstract: Introduction: The prognosis for metastatic colorectal cancer patients (mCRC) with the BRAF V600E mutation is poor. BRAF V600E mutation frequency is reportedly low among Asians; however, the frequency of the BRAF V600E mutation in right-side colon cancer may not be low, even among Asians. In addition, spatial heterogeneity of BRAF V600E mutations also exists, as for RAS mutations. In this prospective observational study, we evaluated BRAF V600E mutations in cancer tissue and plasma of Japanese right-side colon cancer patients. Method: 215 patients with right-side colon cancer were included. BRAF V600E mutations of cancer tissue and plasma were detected using droplet digital PCR. Blood plasma of patients with BRAF V600E mutations in cancer tissue or plasma was drawn at intervals throughout chemotherapy, and BRAF V600E mutations were evaluated. Results: BRAF V600E mutations were detected in tissue samples from 35 of 215 patients (16.3%, cecum; 22.4%, ascending colon; 17.8%, and transverse colon; 9.0%). BRAF V600E mutations were detected in plasma of 10 of 215 (4.7%) patients. Eight of the ten patients had BRAF V600E mutations in their primary tumours, but two (both were Stage IV) patients did not. Sensitivity of liquid biopsy to detect BRAF V600E mutations was 10.3% (3/29) in Stage I-III patients and 83.3% (5/6) in Stage IV patients. Conclusion: BRAF V600E mutations are observed in right-side colon cancer at high frequency, especially in the cecum. BRAF V600E mutations can be detected in plasma and the detection rate is high in patients with advanced cancer. Spatial heterogeneity was observed using liquid biopsy.